IEEE 802.11‐enabled wake‐up radio system: design and performance evaluation. Issue 20 (1st September 2014) - Oller, J.; Garcia, E.; Lopez, E.; Demirkol, I.; Casademont, J.; Paradells, J.; Gamm, U.; Reindl, L.
Abstract : Today, the vast majority of personal communication devices, such as laptops, smartphones, and logically wireless fidelity (Wi‐Fi) access points feature IEEE 802.11 chipsets. In turn, wake‐up radio (WuR) systems are used to reduce the significant energy waste that wireless devices cause during their idle communication mode. A novel WuR system is introduced that enables any IEEE 802.11‐enabled device to be used as a WuR transmitter without requiring any hardware modification. The corresponding developed WuR receiver achieves a remarkably low power consumption of 10.8 μW and operates in the Wi‐Fi 2.4 GHz band. By means of thorough physical tests, it is shown that the proposed IEEE 802.11‐based WuR system enables important energy savings.